Percutaneous microwave ablation on management of hereditary renal cell carcinoma in Von Hippel–Lindau disease - Jiye Chen; Lin Zheng; Wei Zhang; Zhen Wang; Jie Yu; Ping Liang (International Journal of Hyperthermia)
Background The effect of microwave ablation (MWA) for the renal cell carcinoma (RCC) in Von Hippel-Lindau (VHL) disease is unclear.Objective To assess the safety, Technique efficacy, renal function and oncological outcome of MWA for RCC in VHL patients.Methods Consecutive patients with RCCs in VHL disease treated by MWA were retrospectively collected from November 2009 to October 2020. The technical efficacy rate and complications were assessed. The outcomes of pre- and post-ablative eGFR were compared. The local recurrent-free survival (LRFS), renal-cancer-free survival (RCFS), cancer-specific survival (CSS), overall survival (OS) and complications were presented.Results A total of 10 patients (mean age, 39.0 years ± 10.7 [SD]; 3 women) with 28 RCCs (mean tumor size, 3.0 cm ± 0.34; mean tumor volume, 20.7 mL ± 43.3) treated with MWA were included. Th median follow-up time was 52 months(IQR:27-80). The overall technical efficacy rate was 100% with no major complications occurred. No significant statistical difference between pre-ablative and postablative creatinine level (102.0 µmol/L ± 30.4 vs 112.3 µmol/L ± 38.7, p = 0.06), but the pre-ablative eGFR level was significantly higher than the post-ablative eGFR (78.0 mL/(min*1.73m2) ± 28.6 vs 72 mL/(min*1.73m2) ± 31.4, p = 0.04), with the mean decrease of 5.86 ml/(min*1.73m2). The local recurrent-free survival(LRFS) and renal-cancer-free survival (RCFS) were 100% and 60%, respectively. The cancer specifical survival (CSS) and overall survival (OS) were 95.5% and 100%, respectively.Conclusion Microwave ablation is a safe and feasible method for the treatment of RCC in VHL disease, preserving renal function and yielding satisfactory oncological outcomes.